Epithelial–Mesenchymal Transition in Ovarian Carcinoma - Davidson, Ben; Trope, Claes G.; Reich, Reuven (Frontiers in Oncology, 2012)
Ovarian cancer is the most lethal gynecologic malignancy, with the majority of patients dying within 5 years of diagnosis. This poor survival of patients diagnosed with this malignancy is attributed to diagnosis at advanced stage, when the tumor has metastasized, and to chemotherapy resistance, either primary or developing along tumor progression. However, ovarian carcinomas, constituting the vast majority of ovarian cancers, additionally have unique biology, one aspect of which is the ability to co-express epithelial and mesenchymal determinants. Epithelial-mesenchymal transition (EMT), a physiological process by which mesenchymal cells are formed and migrate to target organs during embryogenesis, is involved in cancer cell invasion and metastasis. However, these changes do not fully occur in ovarian carcinoma, and are even reversed in tumor cells present in malignant peritoneal and pleural effusions. This review summarizes current knowledge in this area, including the characteristics of EMT related to adhesion, transcriptional regulation and chemoresistance, and their clinical relevance, as well as the recently observed regulation of EMT by microRNA.